Pengembangan Media Berbasis Aplikasi Assemblr Edu Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas V MI Ihyaul Ulum Ngambeg-Lamongan - Choirunnisa', Hanim Afidlotul; Mufidah, Eli (IBTIDA', 2023)
Assemblr Edu application to improve student learning outcomes. Knowing the level of product validity and proving an increase in learning outcomes for class V students at MI Ihyaul Ulum Ngambeg. This research method uses Research and Development (R&D) research using the ADDIE development model such as Analyze, Design, Development, Implementation, and Evaluation. The sample in this study were students of class V, totaling 40 students. The research instrument used a questionnaire and tests. The analysis technique used is descriptive qualitative and quantitative analysis. Based on the results of the expert validation test questionnaire data analysis, the percentage calculation results for material experts were 86%, media experts 92.3%, linguists 94% and practitioner experts 92%, all in the "very good" category. For the study results of the hydrological cycle material showed a significant increase, three times the pre-test showed values ​​of 49, 50 and 53.5 with the less good category increasing in the post-test results to 90, 90.5 and 91 with the very good category. So, it can be concluded that interactive learning media based on the assemblr edu application on hydrological cycle material can improve learning outcomes for students of class V MI Ihyaul Ulum.